DAMPAK PASAR BEBAS ASEAN (MEA) TERHADAP PERTUMBUHAN UMKM PROVINSI RIAU (INDUSTRI MAKANAN BOLU KEMBOJO) - Delasari, Yulia; ", Pazli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
ASEAN Economic Community/AEC is envisaged not merely as a free trade advocate for member countries of ASEAN, but also acts as an integrated economy that could lead ASEAN to a single market and production base for dealing with world market. Its potential impact on Indonesia’s UMKM, however, needs to be analyzed, given the fact that Riau is one of a large province that is popular with UMKM of Bolu Kemojo. The realization of the ASEAN Community in which there is AEC, can make ASEAN into a more strategic position in the international arena, we expect the realization of the ASEAN economic community is able to open the eyes of all parties, so that there is a dialogue between sectors that will also be complementary among stakeholders in the State sector of the economy of ASEAN countries. Indonesia, especially Riau challenges ahead to realize meaningful change for the life of people. This opportunity is open, if it’s not immediately used, it will be left behind, because the process is also followed by the motion of other countries and it continues to be unfold.Key words: AEC, UMKM, Home Industry, Bolu Kemojo